1995
DOI: 10.1111/j.1365-2621.1995.tb04552.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Biogenic Amines during Ripening of Dry Sausages as Affected by Starter Culture and Thawing Time of Raw Materials

Abstract: Raw materials affect formation of biogenic amines in dry sausages. Effects of thawing time of raw materials and amine-negative starter culture on amine formation were studied on a pilot scale. The levels of biogenic amines, precursor amino acids, pH, water activity, and microbial counts were measured. Use of starter culture significantly decreased levels of histamine, tyramine and cadaverine formed. The effect of thawing time on formation of biogenic amines was dependent on the use of starter culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 12 publications
2
60
2
1
Order By: Relevance
“…Biogenic amines in food have also been related to the low quality of the raw materials, in which a high proliferation of microorganisms occurs (Suzzi and Gardini, 2003). Besides that, other authors such as Maijala et al, 1995a, Eerola et al, 1998a, Komprda et al, (2001 have confirmed the important role played by the microbiological quality of the raw materials, with other variables such as pH, a w , NaCl, etc., which can impose important effects on the production of biogenic amines in fish products.…”
Section: Discussionmentioning
confidence: 97%
“…Biogenic amines in food have also been related to the low quality of the raw materials, in which a high proliferation of microorganisms occurs (Suzzi and Gardini, 2003). Besides that, other authors such as Maijala et al, 1995a, Eerola et al, 1998a, Komprda et al, (2001 have confirmed the important role played by the microbiological quality of the raw materials, with other variables such as pH, a w , NaCl, etc., which can impose important effects on the production of biogenic amines in fish products.…”
Section: Discussionmentioning
confidence: 97%
“…Optimal hygienic standards should be assured in order to facilitate the dominance of starter bacteria from the early stages of the fermentation (Bover-Cid et al, 2001b, Maijala et al, 1995a, Novella et al, 2004a.…”
Section: Fermentationmentioning
confidence: 99%
“…Together with other biogenic amines, like putrescine or spermidine, it is formed during oxygen-limited decomposition of protein-rich organic matter by decarboxylation of amino acids or by amination of aldehydes and ketones (8,27,30,42,53,54). These putrid-smelling and, at higher concentrations (100 to 400 mg per kg), often toxic compounds play a major role in food microbiology, e.g., as flavoring constituents in the ripening of cheese or as contaminants of fish and meat products, wine, and beer (24,29,49).…”
mentioning
confidence: 99%